2005
DOI: 10.1016/j.cmet.2005.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The FFA receptor GPR40 links hyperinsulinemia, hepatic steatosis, and impaired glucose homeostasis in mouse

Abstract: Obesity is typically associated with elevated levels of free fatty acids (FFAs) and is linked to glucose intolerance and type 2 diabetes. FFAs exert divergent effects on insulin secretion from beta cells: acute exposure to FFAs stimulates insulin secretion, whereas chronic exposure impairs insulin secretion. The G protein-coupled receptor GPR40 is selectively expressed in beta cells and is activated by FFAs. We show here that GPR40 mediates both acute and chronic effects of FFAs on insulin secretion and that G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
362
14
8

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(408 citation statements)
references
References 61 publications
24
362
14
8
Order By: Relevance
“…There is a firm consensus that GPR40 is expressed in β-cells and this has been confirmed at the mRNA level in a range of species including mouse [23], rat [24] and man [25].…”
Section: Expression Of Gpr40mentioning
confidence: 90%
See 2 more Smart Citations
“…There is a firm consensus that GPR40 is expressed in β-cells and this has been confirmed at the mRNA level in a range of species including mouse [23], rat [24] and man [25].…”
Section: Expression Of Gpr40mentioning
confidence: 90%
“…In particular, it is known that prolonged elevation of circulating fatty acids leads to a decline in insulin secretion and, ultimately, to loss of β-cell viability but there are conflicting views as to the role played by GPR40 in these processes. Initial data were provided by Steneberg and colleagues [64] who generated GPR40 knock-out (KO) mice and observed that, when maintained on a high fat diet, these animals failed to develop the characteristic metabolic abnormalities seen in wild type animals. Specifically, the GPR40 KO animals had lower fasting insulin, greater insulin Page 9 of 34 A c c e p t e d M a n u s c r i p t sensitivity and improved glucose tolerance than the animals with normal levels of GPR40 expression.…”
Section: Role Of Gpr40 In Lipotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…These events may very well be driven by the increased flux of NEFA that arises in the mice as a consequence of HF feeding. The fact that beta cells express G-protein-coupled receptors that utilise NEFA as ligands, the GPR 40 family [27][28][29], raises the possibility that receptor-mediated events triggered by lipids account, at least partially, for the mitochondrial adaptation. Whereas the physiological role of the GPR 40 receptors is still unresolved, our present findings point to an interesting area of beta cell physiology that could be examined with GPR 40 receptors in mind.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinsulinaemia compensates for insulin resistance to maintain normoglycaemia. However, hyperinsulinaemia per se deteriorates insulin resistance [6] and is thought to trigger the progression of the metabolic syndrome [7,8]. The mechanisms linking obesity and insulin resistance to hyperinsulinaemia and beta cell hyperplasia are incompletely understood [3].…”
mentioning
confidence: 99%